Coprophilous ascomycetes of the Oleshkivski Pisky National Nature Park (Kherson region, Ukraine) (CHORNOMORSKI BOTANICAL JOURNAL, 2021)
As a result of mycological research 34 species of coprophilous ascomycetes from 14 genera, 10 families, and 5 orders were recorded on the territory of the Oleshkivski Pisky National Nature Park. Among them 15 species belonged to the class Sordariomycetes, 12 – to Dothideomycetes, and 7 – to Pezizomycetes. Among the orders of the fungi, Sordariales – 12 species, Pleosporales – 11, and Pezizales – 7, occupy the leading position; the rest of the orders revealed the fewer number of species. Among the families, Sporormiaceae, Podosporaceae, Coniochaetaceae, Delitschiaceae, and Sordariacea, were the most abundant regarding the number of species and specimens. The species from the five leading families represent 64,7% of the total number of identified species. Among the found genera of the coprophilous ascomycetes, Coniochaeta, Delitschia, Sordaria, Sporormiella, and Triangularia prevailed by number of species, demonstrating much larger diversity, than others. Environmental conditions inside the park are more favorable for the development of loculoascomycetes and pyrenomycetes. The discomycetes species diversity was much less. The list of recorded fungi and their substrates is presented. All species of ascomycetes were collected on the hare and cattle excrements. Other dung types have not been studied. 31 species are new to the territory of the park, 15 species are new records for the steppe zone of Ukraine. Coniochaeta hansenii and Sporormiella tetramera are first recorded in Ukraine. Descriptions, illustrations, synonyms and general distribution are provided for them. C. hansenii is a fairly common and widespread species in the world, occurring mainly on the leporid droppings. In the park, this species was also collected on hare dung. S. tetramera also belongs to the widespread but rare species of coprophilous ascomycetes, known from isolated records in a few countries. It was collected on the hare excrements in the park. Сoniochaeta leucoplaca, Delitshia perpusilla and Triangularia comata were collected for the first time in the steppe zone of Ukraine and for the second time in the country.
Keywords: protected areas, biodiversity, fungi, Ascomycota, species composition, Coniochaeta hansenii, Sporormiella tetramera.